Development of Village Industry Through an Integrated Information System in Nagari Simarasok, Baso Agam District - Abbas, Ardi; Alfitri, Alfitri; Indraddin, Indraddin (Jurnal Ilmiah Ekotrans & Erudisi, 2024)
The problems of Simarasok UMKM were identified: (1). The products have not been maximized due to marketing weaknesses, capital, and the purchasing power of woven/songket products tends to decrease, (2). Embroidery UMKM are part-time livelihoods for unmarried women and housewives, (3). There is no group of innovative skilled workers, (4). Marketing strategies are more on personal relationships, close proximity and less online sales, (5). Product quality/quantity can be improved, but constrained by external internal factors. The research used qualitative techniques and descriptive analysis; informants were collected by purposive sampling. Data findings, there are specialties of UMKM: 1). The embroidery industry has developed and is carried out by almost half of the female population, 2). Sugarcane and tobacco processing industry, conducted by men. There is a difference between the type of industry and the gender of the actors, which is not interchangeable. 3). Based on scale, the industries are small. Interestingly, UMKM development is carried out through an integrated information system. Although located in rural areas, Nagari Simarasok has utilized spatial technology as an integrated information system in mapping the condition of its UMKM. In this Nagari, a complete map with specifications such as maps of industrial asset ownership, maps of agricultural land potential, maps of economic potential and maps of natural resource potential can be accessed. With the completeness of the map, access to buyers, consumers and or other parties can more easily access it.  This Nagari breakthrough has not even existed in urban villages in the city center.